Correlates of academic -stress among students with hearing impairment in Ibadan, Oyo state, Nigeria (2018)
This study investigated the correlates academic stress among students with hearing impairment in Ibadan, Nigeria. The descriptive survey research design of the correlational type was used to carry out the study. A total of 100 hundred students with hearing impairment from three secondary schools were selected using purposively sampling technique. Four instruments namely: academic stress scale, self-concept inventory, parental involvement scale and emotional intelligence Questionnaire were used for data collection. Three research questions were raised to guide the conduct of the study. Data were analysed using Pearson Product Moment Correlation Coefficient and Multiple Regression. Results showed that there was a significant relationship between Emotional Intelligence, Self Concept, Parental Involvement and Academic Stress among students with hearing impairment. Also, there was significant joint contribution of emotional intelligence, self-concept and parental involvement to academic stress. The relative contribution of the independent variables to dependent variable showed the following order: self-concept, emotional intelligence and parental involvement. It was recommended that the parents and teachers should help the students with hearing impairment reduce academic stress among them.